(3GdebGeI GdMLjIs - (3GejQRG Hf eMeO MSjf GdcQcGfjs ((3MSf GdMSjfi s)
(3ChdgG (B:s
(3Mci JjS Hf UahGf bGd(B: (3GSJfeJ LHdg GdLed, QMdkG Yf HdGO GdLHd s
(3BNQgG (B:s
(3Ch Cdbi ai LfM GdXdeGA , Ch GHJZi fabkG ai GdCQV h oSdekG ai GdSeGA Je GdebGeI s
(3CdagG ai TgQQLH SfI (B1295(3g`s
(3cJHJ ai TgQ hSfI GdJCdjas
(3hHgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs